2017
DOI: 10.1007/s11192-017-2499-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study on Australian academic science

Abstract: As at the end of 2009, 50 million scholarly papers were in existence, and changes in the global higher education sector are seeing this number grow rapidly. With the impact of university ranking schemes, dramatic changes have occurred in the academic publication system; both the number of publications, and the number of scholars, are increasing rapidly. In this research, we conduct a focused study on the quantitative relationships in Australian academic science. Sample data is selected from three institutions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…The overall decline agrees with a study of three social sciences in the U.S. (Sugimoto et al, 2016) but sharply contrasts with the increase in field normalized average citations after age 50 found in Quebec, Canada (Gingras et al, 2008) either because of country or language issues or the use of the arithmetic mean in the latter study. The overall decline also contrasts with the midcareer average citation peak in Australia, although this data was not field normalized (Gu & Blackmore, 2017). As a previous study has shown different career citation patterns in some respects for different disciplines in the United States (Kolesnikov, Fukumoto, & Bozeman, 2018), the overall decreasing trend found here may well not apply to all U.S. fields.…”
Section: Discussioncontrasting
confidence: 72%
“…The overall decline agrees with a study of three social sciences in the U.S. (Sugimoto et al, 2016) but sharply contrasts with the increase in field normalized average citations after age 50 found in Quebec, Canada (Gingras et al, 2008) either because of country or language issues or the use of the arithmetic mean in the latter study. The overall decline also contrasts with the midcareer average citation peak in Australia, although this data was not field normalized (Gu & Blackmore, 2017). As a previous study has shown different career citation patterns in some respects for different disciplines in the United States (Kolesnikov, Fukumoto, & Bozeman, 2018), the overall decreasing trend found here may well not apply to all U.S. fields.…”
Section: Discussioncontrasting
confidence: 72%
“…In other disciplinary fields MPR becomes effective through auto-metrification and peer pressure (see also Flink and Simon 2014). Future research with larger datasets and comparisons between countries with a weak and a strong metric culture are needed to elaborate the mechanisms further, for example in relation to accountability (e.g., Hammarfelt and de Rijcke 2015) and the impact of university ranking schemes (e.g., Gu and Blackmore 2017).…”
Section: Discussion Of Results and Conclusionmentioning
confidence: 99%
“…Although career trajectories for domestic or national researchers have been investigated for the USA (Thelwall, & Fairclough, 2020), and another study has used different methods with a similar goal for Australia (Gu & Blackmore, 2017) and worldwide career impact changes have been reported as part of a study of productivity (Larivière & Costas, 2016), this is apparently the first internationally comparative longitudinal career impact study using reasonably comprehensive journal article data. The focus is on the Scopus-indexed publications of domestic researchers for pragmatic reasons.…”
Section: Introductionmentioning
confidence: 99%